2023
DOI: 10.3390/ma16103633
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Use of Osteobiologic and Metallic Biomaterials in Orthopedic Surgery: The Present and the Future

Abstract: As the area and range of surgical treatments in the orthopedic field have expanded, the development of biomaterials used for these treatments has also advanced. Biomaterials have osteobiologic properties, including osteogenicity, osteoconduction, and osteoinduction. Natural polymers, synthetic polymers, ceramics, and allograft-based substitutes can all be classified as biomaterials. Metallic implants are first-generation biomaterials that continue to be used and are constantly evolving. Metallic implants can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…Cobalt is a widely used component in industry and daily life, and is a major component of biomedical implants, particularly in orthopedic applications [ 1 ]. Recent studies have revealed potential nanoparticle release upon implantation, which can lead to the accumulation and migration of particles, resulting in adverse effects such as renal fibrosis and neural damage [ 3 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cobalt is a widely used component in industry and daily life, and is a major component of biomedical implants, particularly in orthopedic applications [ 1 ]. Recent studies have revealed potential nanoparticle release upon implantation, which can lead to the accumulation and migration of particles, resulting in adverse effects such as renal fibrosis and neural damage [ 3 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metal implants have revolutionized treatment options for many patients in modern medicine. Cobalt alloys, due to their mechanical robustness and biocompatibility, are commonly used in the manufacture of implants, such as artificial joints, bone plates, and screws [ 1 ]. The number of applications for cobalt alloys is increasing every year, and millions of tons of cobalt alloys are used each year in the manufacturing of implants [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in the design of modern orthopedic implants have been greatly enhanced by the development of composite materials [1]. Several metallic, ceramic, and polymer-based composite biomaterials have been developed by researchers for various orthopedic applications [2][3][4][5][6]. About 80% of orthopedic implants are metal-based due to their excellent biocompatibility and superior mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The use of other alternative osteobiologics in spine surgery is believed to improve pain, fusion rates, and clinical outcomes [ 5 ]. At present, autogenic bone grafting has been largely replaced by allogenic bone grafting with comparable results [ 5 , 17 , 18 ]. Additionally, DBM is a widely used allogenic bone substitute, which is produced by removing cellular and mineral components from human cortico-cancellous cadaver bone, thus leaving extracellular matrix molecules, including bone morphogenic proteins (BMPs) with some osteo-inductive effect.…”
Section: Introductionmentioning
confidence: 99%